Double or dual stimulation in poor ovarian responders: where do we stand? - Mehtap Polat; Sezcan Mumusoglu; Irem Yarali Ozbek; Gurkan Bozdag; Hakan Yarali (SAGE Publishing, 2021)
Recent advances in our recognition of two to three follicular waves of development in a single menstrual cycle has challenged the dogmatic approach of ovarian stimulation for in vitro fertilization starting in the early follicular phase. First shown in veterinary medicine and thereafter in women, luteal phase stimulation-derived oocytes are at least as competent as those retrieved following follicular phase stimulation. Poor ovarian responders still remain a challenge for many decades simply because they do not respond to ovarian stimulation. Performing follicular phase stimulation and luteal phase stimulation in the same menstrual cycle, named as double stimulation/dual stimulation, clearly increases the number of oocytes, which is a robust surrogate marker of live birth rate in in vitro fertilization across all female ages. Of interest, apart from one study, the bulk of evidence reports significantly higher number of oocytes following luteal phase stimulation when compared with follicular phase stimulation; hence, performing double stimulation/dual stimulation doubles the number of oocytes leading to a marked decrease in patient drop-out rate which is one of the major factors limiting cumulative live birth rates in such poor prognosis patients. The limited data with double stimulation/dual stimulation-derived embryos is reassuring for obstetric and neonatal outcome. The mandatory requirement of freeze-all and lack of cost-effectiveness data are limitations of this novel approach. Double stimulation/dual stimulation is an effective strategy when the need to obtain oocytes is urgent, including patients with malignant diseases undergoing oocyte cryopreservation and patients of advanced maternal age or with reduced ovarian reserve.